Organizational personnel career development - Yu. A. Filyasova (Управление)
The aim of the study is to analyse opportunities for career development of organizational personnel. The object of the study includes processes providing organizational career development. The subject of the research is interdependence between personal professional development of employees and organizational performance. The research methods are description and analysis.The processes providing career progression can be divided into direct, actively encouraging employees to improve professional skills, and indirect, creating favourable work environment and commitment to achieving organizational relevant goals. Under the modern conditions of societal transformations, it is highly important to pay closer attention to interrelation between personal development and organizational aims since a customary vision of career as vertical climbing a corporate ladder is receding into the past. Opportunities for continuous training, entrepreneurial activity, and multiple vacancies are changing a vision of career as a finite process within an organization. An essential role in the system of personnel management should be played by employee career development planning which establishes connections between financial and nonfinancial incentives, on the one hand, and employee performance, on the other hand, – with respect to their personal interests, social characteristics and motivation level.The author concludes that two opposite tendencies influence personnel management system functioning: change and conservation. The necessity for change is caused by transforming market and social conditions, employee personal growth, and organizational life cycle. The tendency for status quo conservation is dictated by the desire of any system for stability and sustainability.